2022
DOI: 10.1002/brb3.2674
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the A118G OPRM1 polymorphism with sociotropy and interpersonal sensitivity

Abstract: Background:The μ-opioid receptor (MOR) plays an important role in social bonding behaviors, while it is implicated in the pathophysiology of depression. It is shown that the A118G polymorphism (rs1799971) of the MOR gene (OPRM1) causes aminoacid exchange from Asn to Asp, and that this polymorphism is associated with altered mu-opioid receptor function. Meanwhile, sociotropy/autonomy and interpersonal sensitivity are personality vulnerabilities to depression characterized by distinctive interpersonal styles. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(72 reference statements)
0
2
2
Order By: Relevance
“…The dispositional interpersonal sensitivity scores were higher in the A/A group than in the A/G ( p = 0.023) and G/G ( p = 0.009) group. 59 The results of this study seem contradictory to the author's view. Thus, because individuals with the A118G allele are hypersensitive to pain, 49 , 50 such individuals are more likely to show the social pain of rejection, given the homology between physical and psychological pain.…”
Section: Opioid Involvement In Rejection Sensitivitycontrasting
confidence: 99%
See 1 more Smart Citation
“…The dispositional interpersonal sensitivity scores were higher in the A/A group than in the A/G ( p = 0.023) and G/G ( p = 0.009) group. 59 The results of this study seem contradictory to the author's view. Thus, because individuals with the A118G allele are hypersensitive to pain, 49 , 50 such individuals are more likely to show the social pain of rejection, given the homology between physical and psychological pain.…”
Section: Opioid Involvement In Rejection Sensitivitycontrasting
confidence: 99%
“…A study has submitted diametrically opposed results. The dispositional interpersonal sensitivity scores were higher in the A/A group than in the A/G ( p = 0.023) and G/G ( p = 0.009) group 59 . The results of this study seem contradictory to the author's view.…”
Section: Opioid Involvement In Rejection Sensitivitycontrasting
confidence: 96%
“…OPRM1 A118G mutation is the most common and reported functional gene. Some studies have shown that its gene mutation reduces the efficacy of various opioids, and patients with GG need more opioids to relieve pain [ 10 13 ].On the other hand, some studies have shown that OPRM1 A118G mutation can enhance the analgesic effect of patients [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…OPRM1 A118G mutation is the most common and reported functional gene. Studies have shown that its gene mutation reduces the efficacy of various opioids, and patients with GG need more opioids to relieve pain [ [14] , [15] , [16] , [17] ]. Other studies have shown that OPRM1 A118G mutation can enhance the analgesic effect of patients [ [18] , [19] , [20] , [21] ].…”
Section: Discussionmentioning
confidence: 99%